MEMBACA PEMAHAMAN MENGGUNAKAN MODEL KOOPERATIF TIPE STUDENT TEAM ACHIEVEMEN DIVISION (STAD) BAGI SISWA KELAS V SD - zal, hendri; Sukma, Elfia; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The background of this study is the lack of reading comprehension. The purpose of this research in general to increase the ability to read the understanding of grade V students of SD Negeri 04Pasar Surantih Pesisir Selatan Regency with STAD model. This research is a class action research. The research subject is 23 students and researchers. The results of this study show the average value in the stage prabaca is 65.2, the current reading stage only reaches 67.9, while in the post-reading stage 79.6. It occurs in cycle II with an average grade of 83.5. Prabaca stage in cycle II is increased to 76.0, then at the second reading stage is when the reading reaches the number 84.8, pascabaca stage managed to reach an average of 89.6. From the results of this study can be concluded STAD model can improve reading comprehension skills of grade V students of SD Negeri 04 Pasar Surantih Pesisir Selatan Regency.Keywords: Reading understanding, STAD